McPeople and their Predators or about Vampires Going on a Diet - Izdebska, Agnieszka (Porównania, 2022)
The text is an attempt to demonstrate how stories about vampires—ubiquitous in contemporary culture—fit into an accessible version of the issues raised within animal studies. Since the character of the vampire is one of those elements of the Gothic canon that has undergone a dizzying transformation ( there seems to be more differences than shared features between Bram Stoker’s Dracula and Stephenie Meyer’s Twilight heroes ), the article examines the reasons for such a radical change in our stories about fictitious creatures that we have placed above us in the food chain. Jim Jarmusch’s film Only Lovers Left Alive has been analysed in more detail in the article; however, other ( apart from the already mentioned ) “canonical” texts are mentioned, such as Interview with the Vampire by Anne Rice, and some less known ones, including Suzy McKee-Charnas’ The Vampire Tapestry or Truth by Terry Pratchett.